Allocation of Input Use in Dryland Chili Farming of Kelompok Tani Hutan Panderman, Batu City - Palus, Fridolin Triayen; Pudjiastuti, Agnes Quartina; Yoga, Tirta (PT. Riset Press International, 2025)
Chili cultivation in dryland areas faces significant challenges, including limited water availability, low soil fertility, and the risk of land degradation. Under such conditions, the efficient use of inputs becomes a critical factor in enhancing both productivity and the sustainability of farming practices. This study aims to examine the influence of production factors on chili yield and to assess the levels of technical, allocative, and economic efficiency among chili farmers in Kelompok Tani Hutan Panderman. A quantitative approach with a descriptive-analytical method was employed. Primary data were gathered through questionnaires administered to 32 farmers selected via a census method and analyzed using multiple linear regression within a Cobb-Douglas production function framework. The results indicate that land area, labor, and farming experience have a significant positive impact on production, whereas excessive use of urea fertilizer and pesticides exerts a negative effect. While technical efficiency was largely achieved, allocative and economic efficiencies remain suboptimal. These findings highlight the importance of optimizing input allocation, adopting water-saving technologies, and implementing balanced fertilization strategies. The study’s implications point toward strengthening agricultural extension services, promoting appropriate technology adoption, and enhancing farmers’ managerial capacities to achieve sustainable productivity and efficiency.